2018
DOI: 10.1001/jamacardio.2018.3408
|View full text |Cite|
|
Sign up to set email alerts
|

Timing of Loading Dose of Atorvastatin in Patients Undergoing Percutaneous Coronary Intervention for Acute Coronary Syndromes

Abstract: IMPORTANCE Loading doses of atorvastatin did not show reduction on clinical outcomes in the overall population of patients with acute coronary syndrome (ACS) enrolled in the Statins Evaluation in Coronary Procedures and Revascularization (SECURE-PCI) trial, but a potential benefit was identified in patients who subsequently underwent percutaneous coronary intervention (PCI). OBJECTIVES To determine whether periprocedural loading doses of atorvastatin are associated with decreased 30-day major adverse cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“… 8 Contudo, um ensaio randomizado mais amplo, o SECURE-PCI, não detectou uma redução em eventos isquêmicos pós SCA com atorvastatina precoce na dose de 80 mg, 9 apesar do potencial benefício no subgrupo de pacientes submetidos à ICP após a randomização. 30 …”
Section: Discussionunclassified
See 1 more Smart Citation
“… 8 Contudo, um ensaio randomizado mais amplo, o SECURE-PCI, não detectou uma redução em eventos isquêmicos pós SCA com atorvastatina precoce na dose de 80 mg, 9 apesar do potencial benefício no subgrupo de pacientes submetidos à ICP após a randomização. 30 …”
Section: Discussionunclassified
“… 8 However, a larger randomized study, the SECURE-PCI trial, did not find a decrease in ischemic events after ACS with an 80 mg loading dose of atorvastatin, 9 despite a potential benefit in the subgroup of patients who were submitted to PCI after randomization. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin and rosuvastatin are both high-intensity statins recommended by current guidelines as first-line therapy in ACS patients [3]. The correct timing of statin administration during the index event is still being debated [3, 33, 34]. Originally, statin prescription was recommended at discharge after an episode of ACS [35].…”
Section: Discussionmentioning
confidence: 99%
“…The time of administration was further anticipated in the first PRATO-ACS trial involving statin-naive patients with NSTEACS; early on-admission rosuvastatin resulted in a significantly lower incidence of AKI and improved 30-day and 6-month clinical outcomes, which was statistically significant in patients subjected to PCI [4]. A very recent randomized trial in 4,191 patients with ACS and a planned invasive strategy showed short-term (30 days) clinical benefits of a preprocedural high-dose atorvastatin load only in patients subjected to PCI and in patients with STEMI [33]. The present PRATO-ACS 2 study shows that early on-admission (prior to angiographic procedures) high-intensity statins provide important protection especially regarding renal function that leads to overall clinical benefits at 30 days and 12 months, with impressive better outcome in patients who do not develop AKI or WRF, irrespectively of the choice of statin.…”
Section: Discussionmentioning
confidence: 99%
“…Even though early functionally restored revascularization effectively prevents alterations in ventricular architecture and thereby stop developing early adverse cardiac remodeling, there is no compelling evidence that late adverse cardiac remodeling could be effectively prevented by restoring coronary blood flow beyond the use of peri-procedural and post-procedural drugs (i.e., statins, double anti-platelet therapy, abciximab, tirofiban, ACE inhibitors, etc.) [9][10][11][12] . In this context, biomarkers would be a useful tool to indicate whether candidates for PCI are at high risk of poor clinical outcomes relating to late adverse cardiac remodeling and whether they should be treated by an alternative method.…”
Section: Introductionmentioning
confidence: 99%